O discurso sobre as cotas para negros na revista Veja. - Oliveira, Luiz Carlos de (2013)
In this study, I discuss the discourse about the quotas for black people in the pages of Veja magazine. I established as a time frame for the research the years from 2009 to 2011. The main question of the study is to set how the discourse in the weekly magazine is constituted. Thus, the central objective of this work, supported by the theoretical principles of the French Discourse Analysis, is to comprehend how the discursive process about the quotas for black people in the magazine is constituted during the established time frame, time in which the topic is in a strong debate in the National Congress of Brazil and in the Federal Supreme Court, also gaining the pages of the press. The study is based mainly on studies of Mariani (1998), Moura (2004), Orlandi (2007a [1999], 2007b [1992]) and Pêcheux (2009 [1988], 2008 [1990]). Through online research at the address <http://veja.abril.com.br/acervodigital/>, it was possible to search the texts that discussed the quotas for blacks. The search for texts online was guided by prior establishment of keywords: affirmative action, affirmative action policies, quotas, racial quotas, university reserving quotas, race, miscegenation, black (male, female), blacks, African descendant, African descendants, discrimination, prejudice, racism. The keywords were considered from the pre-reading of magazine s reports in which the discussion about the quotas occurred and from the objectives set for the research: to highlight the strategies used in the discursive constitution of Veja as a way to organize and support its discourse; to reflect the conditions of production that mark the production of discourse about the topic; to comprehend what imaginary about the black is present in the magazine s discourse to address the quotas; by highlighting the discursive formations prevalent in the analysis of the corpus, to bring the main aspects of the discursive process about the quotas for black people. For the analysis, I selected discursive sequences considering the paraphrastic course, i.e., the reinforcement and the sedimentation of determined meaning effects about the topic in the pages of the weekly magazine. Besides, I selected for analysis eight reader s letters and nine photographs. I structured the discussion guided by three articulated axis that constitute this study: the historical feature about the presence of blacks in Brazil and its developments; theoretical questions that involve the press; and finally the analysis of the corpus. It can be concluded that, supported by the pre-constructed of racial democracy and individual merit allied to legal equality, Veja opposes the quotas for blacks and, for that, mobilizes the discourse of experts and blacks against the quotas and the discourse of science, silencing the claims of pro-quota movements and pointing to other mechanisms that enable the integration of blacks that do not consider the quotas. Producing, therefore, meaning effects of danger , risk , political and ideological interference of the Worker s Party federal government and racialization of the country. In this process, the black is imaginatively produced in a dual way, good or bad, according to the discursive positions supported by the magazine.